TBC battery grooving method and TBC battery preparation method and application

By using a combination of laser patterning and thermal oxidation in the N region of the TBC cell, the BSG layer and tunneled oxide layer are removed, and the problem of insufficient laser energy in the prior art is solved, and the absorption of long-band light and cell conversion are improved. efficiency.

CN119208441AActive Publication Date: 2024-12-27DONGFANG HUANSHENG PHOTOVOLTAIC (JIANGSU) CO LTD

Patent Information

Application Number
CN202411295998.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-27
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

During the N-zone slotting process of existing TBC cells, the laser energy limitation leads to a reduction in the absorption of long-band light, thereby reducing the current and conversion efficiency.

Method used

The BSG layer and tunneling oxide layer in the preset negative electrode region are removed by laser patterning + thermal oxidation + laser patterning to avoid damaging the silicon matrix and improve the absorption of long-band light.

Benefits of technology

The conversion efficiency of the battery is improved, the number of photogenerated carriers is increased, and the current output is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208441A_ABST
    Figure CN119208441A_ABST
Patent Text Reader

Abstract

The invention provides a TBC cell grooving method and a TBC cell preparation method and application, and relates to the technical field of solar cells, and the TBC cell grooving method comprises the following steps: preparing a first tunneling oxide layer, a P-Poly layer and a first BSG layer on the back surface of a cell substrate in sequence, and removing the first BSG layer in a preset negative electrode region through first laser treatment; and carrying out thermal oxidation treatment on the P-Poly layer to oxidize the P-Poly layer in the preset negative electrode region into a second BSG layer, and removing the second BSG layer and the first tunneling oxide layer in the preset negative electrode region by adopting second laser treatment to obtain the cell with the groove in the preset negative electrode region. According to the invention, a mode of laser patterning, thermal oxidation and laser patterning preparation is adopted at the slotting position of the preset negative electrode region, so that the silicon substrate is not damaged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a TBC battery grooving method and a TBC battery preparation method and application. Background Art

[0002] The front of the IBC cell is unobstructed and has higher conversion efficiency. The IBC (Interdigitated back contact) cell is also called the interdigitated back contact cell. Its characteristic is that all the grid lines on the front of the cell are transferred to the back, which reduces the obstruction of the incident light and improves the short-circuit current and conversion efficiency of the cell. The BC cell is a platform technology that can be combined with X cells using different passivation processes to form various XBC cells, such as combining with Topcon to form TBC cells. The PECVD process route is generally: double-sided polishing - PECVD preparation of P-poly - back patterning - polishing - PECVD preparation of N-poly - annealing - secondary patterning - cleaning + texturing - double-sided ALOx - back SiNx - front SiNx - printing - light injection - testing.

[0003] The existing TBC battery N-region slots are prepared by back-side patterning and polishing. First, the back BSG is slotted using a laser. Due to the limited laser energy, the P-poly and tunnel oxide layers are retained. Then, alkaline solution is used for polishing to remove the P-poly and tunnel oxide layers. However, the alkaline solution will also corrode the silicon substrate at the same time. The greater the corrosion depth, the less the absorption of long-wave incident light, the fewer photogenerated carriers, the lower the current, and ultimately the lower the efficiency.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One of the purposes of the present invention is to provide a TBC battery slotting method to at least solve one of the technical problems existing in the prior art. The TBC battery slotting method comprises the following steps: sequentially preparing a first tunneling oxide layer, a P-Poly layer and a first BSG layer on the back of the battery substrate, and removing the first BSG layer in the preset negative electrode area by a first laser treatment; then thermally oxidizing the P-Poly layer to oxidize the P-Poly layer in the preset negative electrode area into a second BSG layer, and removing the second BSG layer and the first tunneling oxide layer in the preset negative electrode area by a second laser treatment, to obtain a battery cell slotted in the preset negative electrode area. The present invention adopts the method of laser patterning + thermal oxidation + laser patterning for the slotting of the preset negative electrode area, which will not damage the silicon substrate.

[0006] A second object of the present invention is to provide an application of the TBC battery slotting method in the preparation of TBC batteries.

[0007] The third object of the present invention is to provide a method for preparing a TBC battery. The method for preparing a TBC battery comprises the following steps: sequentially preparing a second tunneling oxide layer, an N-Poly layer and a PSG layer in the slotted area of ​​the battery cell obtained by the TBC battery slotting method, and annealing and crystallizing; removing the PSG layer in the preset positive electrode area and the PSG layer in the Gap area, and then removing the N-poly layer, the second tunneling oxide layer, and the first BSG layer in the preset positive electrode area, and removing the PSG layer in the preset negative electrode area, and removing the N-poly layer and the second tunneling oxide layer in the Gap area; preparing a passivation film on both sides of the battery cell, and then metallizing the battery cell to prepare a TBC battery. When the present invention removes the BSG layer, P-poly, and tunneling oxide layer in the preset negative electrode area when preparing the TBC battery, the silicon substrate is not damaged, the absorption of long-wavelength light is improved, the number of photogenerated carriers is increased, the current is increased, and the conversion efficiency of the battery is finally improved.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] In a first aspect, the present invention provides a TBC battery slotting method, the TBC battery slotting method comprising the following steps:

[0010] A first tunneling oxide layer, a P-Poly layer and a first BSG layer are sequentially prepared on the back side of the battery substrate, and the first BSG layer of the preset negative electrode region is removed by a first laser treatment;

[0011] The P-Poly layer is then thermally oxidized to oxidize the P-Poly layer in the preset negative electrode region into a second BSG layer. A second laser treatment is performed to remove the second BSG layer and the first tunneling oxide layer in the preset negative electrode region to obtain a battery cell with a groove in the preset negative electrode region.

[0012] In the present invention, the TBC battery slotting method provided by the present invention adopts laser patterning + thermal oxidation + laser patterning to slot the preset negative electrode area (N area) of the TBC battery. First, laser patterning is used to remove the first BSG layer at the slotting location, and then the P-Poly layer is oxidized by thermal oxidation to oxidize the P-Poly layer in the preset negative electrode area into a second BSG layer. This is because silicon and silicon dioxide have different absorption characteristics for lasers. Laser etching cannot directly etch silicon, but can only etch silicon oxide. Therefore, the P-Poly layer is oxidized to form a BSG layer, and then laser patterning is used to remove the newly formed BSG layer and the remaining tunneling oxide layer.

[0013] Preferably, the first tunnel oxide layer, the P-Poly layer and the first BSG layer are deposited by a PECVD process;

[0014] Preferably, the thickness of the first tunnel oxide layer is 0.8-2.0 nm, for example, 0.8 nm, 0.9 nm, 1 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, 1.8 nm, 1.9 nm, 2.0 nm, etc.;

[0015] Preferably, the thickness of the P-Poly layer is 100-300 nm, for example, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, etc.;

[0016] Preferably, B2H6, SiH4 and H2 are introduced into the PECVD equipment to deposit the P-Poly layer, the deposition temperature is 300-400°C, for example, it can be 300°C, 350°C, 400°C, etc., the deposition time is 10-40min, for example, it can be 10min, 15min, 20min, 25min, 30min, 35min, 40min, etc., the gas flow ratio of SiH4, H2 and B2H6 is 1:(9-12):(2-5), "9-12" can be, for example, 9, 10, 11, 12, etc., and "2-5" can be, for example, 2, 3, 4, 5, etc.; the gas flow rate of H2 is 2000-8000sccm, for example, it can be 2000sccm, 3000sccm, 4000sccm, 5000sccm, 6000sccm, 7000sccm, 8000sccm, etc.

[0017] Preferably, the thickness of the first BSG layer is 30-100 nm, for example, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.;

[0018] Preferably, N2O, SiH4, B2H6 and H2 are introduced into the PECVD device to deposit the first BSG layer, the deposition temperature is 300-350°C, for example, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, etc., the deposition time is 70-90min, for example, 70min, 75min, 80min, 85min, 90min, etc., the gas flow ratio of N2O and SiH4 is (5-9):1, for example, 5 : 1, 6:1, 7:1, 8:1, 9:1, etc., the gas flow ratio of B2H6 and SiH4 is (4-10): 1, for example, it can be 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc., and the gas flow rate of H2 is 2000-8000sccm, for example, it can be 2000sccm, 3000sccm, 4000sccm, 5000sccm, 6000sccm, 7000sccm, 8000sccm, etc.

[0019] Preferably, the first laser treatment power is 60-90%, for example, it can be 60%, 65%, 70%, 75%, 80%, 85%, 90% etc., the depth is 30-80nm, for example, it can be 30nm, 40nm, 50nm, 60nm, 70nm, 80nm etc., the width is 400-600nm, for example, it can be 400nm, 450nm, 500nm, 550nm, 600nm etc., the second laser treatment power is 60-90%, for example, it can be 60%, 65%, 70%, 75%, 80%, 85%, 90% etc., the depth is 50-200nm, for example, it can be 50nm, 100nm, 150nm, 200nm etc., the width is 400-600nm, for example, it can be 400nm, 450nm, 500nm, 550nm, 600nm etc.

[0020] Preferably, the thermal oxidation treatment temperature is 700-900°C, for example, it can be 700°C, 750°C, 800°C, 850°C, 900°C, etc., the oxygen flow rate is 8-15slm, for example, it can be 8slm, 9slm, 10slm, 11slm, 12slm, 13slm, 14slm, 15slm, etc., the pressure is 300-700mbar, for example, it can be 300mbar, 350mbar, 400mbar, 450mbar, 500mbar, 550mbar, 600mbar, 650mbar, 700mbar, etc., and the time is 1-2h, for example, it can be 1h, 1.5h, 2h, etc.

[0021] Preferably, the N-type crystalline silicon substrate is preferably a battery substrate.

[0022] In a second aspect, the present invention provides an application of the TBC battery slotting method in the preparation of a TBC battery.

[0023] In a third aspect, the present invention provides a method for preparing a TBC battery, the method comprising the following steps:

[0024] A second tunneling oxide layer, an N-Poly layer and a PSG layer are sequentially prepared in the groove area and the Gap area of ​​the battery cell obtained by the TBC battery groove method, and annealed and crystallized;

[0025] Removing the PSG layer in the preset positive electrode region and the PSG layer in the Gap region, and then removing the N-poly layer, the second tunnel oxide layer, and the first BSG layer in the preset positive electrode region, and removing the PSG layer in the preset negative electrode region, and removing the N-poly layer and the second tunnel oxide layer in the Gap region;

[0026] A passivation film is prepared on both sides of the battery cell, and then the battery cell is metallized to prepare a TBC battery, wherein the Gap region is the partition between the P region (preset positive electrode region) and the N region (preset negative electrode region).

[0027] In the present invention, the preparation method provided by the present invention can improve the battery conversion efficiency of the TBC battery.

[0028] Preferably, the second tunnel oxide layer, the N-Poly layer and the PSG layer are deposited by a PECVD process;

[0029] Preferably, the thickness of the second tunnel oxide layer is 0.8-2.0 nm, for example, 0.8 nm, 0.9 nm, 1 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, 1.8 nm, 1.9 nm, 2.0 nm, etc.;

[0030] Preferably, the thickness of the N-Poly layer is 100-300 nm, for example, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, etc.;

[0031] Preferably, PH3, SiH4 and H2 are introduced into a PECVD device to deposit the P-Poly layer, the deposition temperature is 400-500°C, for example, 400°C, 450°C, 500°C, etc., the deposition time is 10-40min, for example, 10min, 15min, 20min, 25min, 30min, 35min, 40min, etc., the flow ratio of SiH4, H2 and PH3 is 1:(1-3):(0.2-0.5), "1-3" can be, for example, 1, 2, 3, etc., "0.2-0.5" can be, for example, 0.2, 0.3, 0.4, 0.5, etc., the gas flow rate of H2 is 3000-6000sccm, for example, 3000sccm, 4000sccm, 5000sccm, 6000sccm, etc.;

[0032] Preferably, the thickness of the PSG layer is 30-100 nm, for example, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.;

[0033] Preferably, SiH4, N2O, H2 and PH3 are introduced into the PECVD device to deposit the PSG layer, the deposition temperature is 400-500°C, for example, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, etc., the deposition time is 70-90min, for example, 70min, 75min, 80min, 85min, 90min, etc., the N2O and The gas flow ratio of SiH4 is (4-6):1, for example, it can be 4:1, 5:1, 6:1, etc. The gas flow ratio of PH3 and SiH4 is (1-3):1, for example, it can be 1:1, 2:1, 3:1, etc. The gas flow rate of H2 is 3000-6000sccm, for example, it can be 3000sccm, 3500sccm, 4000sccm, 4500sccm, 5000sccm, 5500sccm, 6000sccm, etc.

[0034] Preferably, the annealing temperature is 800-950°C, for example, 800°C, 850°C, 900°C, etc., and the annealing time is 0.5-2h, for example, 0.5h, 1h, 1.5h, 2h, etc.

[0035] Preferably, a third laser treatment is used to remove the PSG layer in the preset positive electrode region and the PSG layer in the Gap region;

[0036] Preferably, the third laser treatment power is 60-90%, for example, it can be 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc., and the depth is 30-80nm, for example, it can be 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, etc.

[0037] Preferably, a cleaning and texturing process is used to remove the N-poly layer, the second tunneling oxide layer, and the first BSG layer in the preset positive electrode region, the PSG layer in the preset negative electrode region, and the N-poly layer and the second tunneling oxide layer in the Gap region;

[0038] In the present invention, a cleaning and texturing process is adopted to retain the N-PolySi layer in the N region on the back of the silicon substrate, and remove the N-PolySi layer in other regions and the BSG layer on the back of the silicon substrate.

[0039] Preferably, the reagent used for cleaning and texturing is NaOH solution with a concentration of 0.4%±0.1%;

[0040] Preferably, preparing the passivation film includes preparing an aluminum oxide layer and a silicon nitride layer.

[0041] Furthermore, the TBC battery preparation method comprises the following steps:

[0042] Step 1: Select an N-type crystalline silicon substrate and perform a double-sided polishing process;

[0043] Step 2: Depositing the first tunnel oxide layer, the P-Poly layer and the first BSG layer on the cell after the treatment in step 1 by PECVD;

[0044] Step 3: Perform the first laser patterning on the cell processed in step 2 to remove the first BSG layer in the preset negative electrode region (N region) on the back of the cell;

[0045] Step 4: thermally oxidize the back side of the cell after the treatment in step 3, so that the P-poly layer exposed in the back N region is oxidized into a second BSG layer;

[0046] Step 5: Performing a second laser patterning on the cell processed in step 4 to remove the newly formed second BSG layer and the remaining first tunnel oxide layer in the N region, thereby obtaining a cell with a groove in the preset negative electrode region;

[0047] Step 6: The second tunnel oxide layer, N-Poly layer and PSG layer are sequentially deposited in the groove area and Gap area of ​​the cell by PECVD;

[0048] Step 7: annealing and crystallization;

[0049] Step 8: Performing a third laser patterning on the cell after the processing in step 7 to remove the PSG layer in the preset positive electrode area and the PSG layer in the Gap area;

[0050] Step 9: Clean and texturize the cell after the treatment in step 8, remove the N-poly layer, the second tunnel oxide layer, and the first BSG layer in the preset positive electrode area, remove the PSG layer in the preset negative electrode area, and remove the N-poly layer and the second tunnel oxide layer in the Gap area;

[0051] Step 10: Prepare aluminum oxide layers on both sides of the battery cell processed in step 9, coat the front and back sides with SiNx films, and then metallize to form a battery.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] The TBC battery slotting method provided by the present invention uses laser patterning + thermal oxidation + laser patterning to slot the preset negative electrode area (N area) of the TBC battery. First, laser patterning is used to remove the first BSG layer at the slotting location, and then the P-Poly layer is oxidized by thermal oxidation to oxidize the P-Poly layer in the preset negative electrode area into a second BSG layer. This is because silicon and silicon dioxide have different absorption characteristics for lasers. Laser etching cannot directly etch silicon, but can only etch silicon oxide. Therefore, the P-Poly layer is oxidized to form a BSG layer, and then laser patterning is used to remove the newly formed BSG layer and the remaining tunneling oxide layer.

[0054] The TBC battery provided by the present invention does not damage the silicon substrate when the BSG layer, P-poly and tunnel oxide layer are removed by grooving in the N region, thereby improving the absorption of long-wavelength light, increasing the number of photogenerated carriers, increasing the current and ultimately improving the conversion efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0056] Figure 1 It is a schematic diagram of the structure in which a first tunneling oxide layer, a P-Poly layer and a first BSG layer are deposited on the back of a battery substrate in the present invention;

[0057] Figure 2 This is a schematic diagram of the cell structure after the first laser patterning;

[0058] Figure 3It is a schematic diagram of a structure in which a second tunnel oxide layer, an N-Poly layer and a PSG layer are deposited in a preset negative electrode region of a battery cell;

[0059] Figure 4 This is a schematic diagram of the cell structure after the third laser patterning;

[0060] Figure 5 This is a schematic diagram of the battery cell structure after cleaning and texturing;

[0061] Figure 6 Schematic diagram of the structure of the prepared TBC battery.

[0062] Icon: 10-first tunneling oxide layer; 20-P-Poly layer; 30-first BSG layer; 40-second tunneling oxide layer; 50-N-Poly layer; 60-PSG layer; 70-N-type crystalline silicon substrate; 80-aluminum oxide layer; 90-silicon nitride layer; 100-silicon oxide layer; 110-P region electrode; 120-N region electrode; 130-N++ layer. DETAILED DESCRIPTION

[0063] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0064] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0065] The present invention provides a method for preparing a TBC battery, comprising the following steps:

[0066] Step 1: Select an N-type crystalline silicon substrate 70 and perform a double-sided polishing process;

[0067] Step 2: The cell treated in step 1 is subjected to PECVD deposition of a first tunnel oxide layer 10, a P-Poly layer 20 and a first BSG layer 30. The cell structure is as follows: Figure 1 shown.

[0068] Step 3: Perform the first laser patterning on the cell after the step 2 to remove the first BSG layer 30 of the preset negative electrode region (N region) on the back of the cell. The cell structure after the first laser patterning is as follows: Figure 2 shown.

[0069] Step 4: thermally oxidize the back side of the cell after the treatment in step 3, so that the P-Poly layer 20 exposed in the back N region is oxidized into a second BSG layer;

[0070] Step 5: Performing a second laser patterning on the cell after the processing in step 4 to remove the newly formed second BSG layer in the N region and the remaining first tunnel oxide layer 10, thereby obtaining a cell with a groove in the preset negative electrode region;

[0071] Step 6: The second tunnel oxide layer 40, N-Poly layer 50 and PSG layer 60 are sequentially deposited in the slotted area and the Gap area of ​​the cell by PECVD. The cell structure is as follows: Figure 3 As shown, the PSG layer 60 and the N++ layer 130 on the front side of the cell are front-side plated layers.

[0072] Step 7: annealing and crystallization;

[0073] Step 8: The cell processed in step 7 is subjected to a third laser patterning to remove the PSG layer 60 in the preset positive electrode area and the PSG layer 60 in the Gap area. The cell structure after the third laser patterning is as follows: Figure 4 As shown;

[0074] Step 9: Clean and texturize the cell after step 8, remove the N-Poly layer 50, the second tunnel oxide layer 40, the first BSG layer 30 in the preset positive electrode area, remove the PSG layer 60 in the preset negative electrode area, and remove the N-Poly layer 50 and the second tunnel oxide layer 40 in the Gap area. The cell structure after cleaning and texturizing is as follows: Figure 5 As shown;

[0075] Step 10: Prepare aluminum oxide layer 80 on both sides of the cell processed in step 9 and plate silicon nitride layer 90 (SiNx film) on the front and back sides, and then metallize to form a cell. The cell structure is as follows: Figure 6 As shown, the slurry is printed through screen printing to form the N-region electrode 120 and the P-region electrode 110, and the silicon oxide layer 100 is plated when silicon nitride is plated on the front side, and is generated by ionization of SiH4 and N2O.

[0076] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0077] Example 1

[0078] This embodiment provides a TBC battery slotting method, comprising the following steps:

[0079] Step 1: Select an N-type crystalline silicon substrate and perform a double-sided polishing process;

[0080] Step 2: Deposit a tunnel oxide layer, a P-Poly layer and a BSG layer on the cell after being processed in step 1 through a PECVD process;

[0081] The thickness of the tunnel oxide layer is 0.8 nm. B2H6 gas is introduced during the Poly deposition process to achieve in-situ doping. The thickness of the P-Poly layer is 300 nm.

[0082] Wherein, B2H6, SiH4 and H2 are introduced into the PECVD equipment to deposit the P-Poly layer, the deposition temperature is 300° C., the deposition time is 40 min, the gas flow ratio of SiH4, H2 and B2H6 is 1:9:5, and the gas flow rate of H2 is 2000 sccm;

[0083] Among them, the thickness of the BSG layer is 30nm, and N2O, SiH4, B2H6 and H2 are introduced into the PECVD equipment to deposit the BSG layer. The deposition temperature is 300°C, the deposition time is 70min, the gas flow ratio of N2O and SiH4 is 5:1, the gas flow ratio of B2H6 and SiH4 is 10:1, and the gas flow rate of H2 is 2000sccm.

[0084] Step 3: Perform the first laser patterning on the cell processed in step 2 to remove the BSG layer of the preset negative electrode region (N region) on the back of the cell;

[0085] The first laser treatment has a power of 60%, a depth of 30 nm, and a width of 400 nm.

[0086] Step 4: thermally oxidize the back side of the cell after the treatment in step 3, so that the P-poly layer exposed in the back N region is oxidized into a BSG layer;

[0087] The thermal oxidation treatment temperature is 700° C., the oxygen flow rate is 15 slm, the pressure is 700 mbar, and the time is 1 hour.

[0088] Step 5: Perform a second laser patterning on the cell after the treatment in step 4 to remove the newly formed BSG layer and the remaining tunnel oxide layer in the N region, and obtain a cell with a groove in the preset negative electrode region;

[0089] The second laser treatment has a power of 60%, a depth of 50 nm, and a width of 400 nm.

[0090] Example 2

[0091] This embodiment provides a TBC battery slotting method, comprising the following steps:

[0092] Step 1: Select an N-type crystalline silicon substrate and perform a double-sided polishing process;

[0093] Step 2: Deposit a tunnel oxide layer, a P-Poly layer and a BSG layer on the cell after being processed in step 1 through a PECVD process;

[0094] The thickness of the tunnel oxide layer is 2.0 nm. B2H6 gas is introduced during the Poly deposition process to achieve in-situ doping. The thickness of the P-Poly layer is 100 nm.

[0095] Wherein, B2H6, SiH4 and H2 are introduced into the PECVD equipment to deposit the P-Poly layer, the deposition temperature is 400°C, the deposition time is 10minmin, the gas flow ratio of SiH4, H2 and B2H6 is 1:12:2, and the gas flow rate of H2 is 8000sccm;

[0096] Among them, the thickness of the BSG layer is 100nm, and N2O, SiH4, B2H6 and H2 are introduced into the PECVD equipment to deposit the BSG layer. The deposition temperature is 350°C, the deposition time is 90min, the gas flow ratio of N2O and SiH4 is 9:1, the gas flow ratio of B2H6 and SiH4 is 4:1, and the gas flow rate of H2 is 8000sccm.

[0097] Step 3: Perform the first laser patterning on the cell processed in step 2 to remove the BSG layer of the preset negative electrode region (N region) on the back of the cell;

[0098] The first laser processing power was 90%, the depth was 80nm, and the width was 600nm.

[0099] Step 4: thermally oxidize the back side of the cell after the treatment in step 3, so that the P-poly layer exposed in the back N region is oxidized into a BSG layer;

[0100] The thermal oxidation treatment temperature is 900° C., the oxygen flow rate is 8 slm, the pressure is 300 mbar, and the time is 2 h.

[0101] Step 5: Perform a second laser patterning on the cell after the treatment in step 4 to remove the newly formed BSG layer and the remaining tunnel oxide layer in the N region, and obtain a cell with a groove in the preset negative electrode region;

[0102] The second laser treatment has a power of 90%, a depth of 200 nm, and a width of 600 nm.

[0103] Example 3

[0104] This embodiment provides a TBC battery slotting method, comprising the following steps:

[0105] Step 1: Select an N-type crystalline silicon substrate and perform a double-sided polishing process;

[0106] Step 2: Deposit a tunnel oxide layer, a P-Poly layer and a BSG layer on the cell after being processed in step 1 through a PECVD process;

[0107] The thickness of the tunnel oxide layer is 1.4 nm. B2H6 gas is introduced during the Poly deposition process to achieve in-situ doping. The thickness of the P-Poly layer is 200 nm.

[0108] Wherein, B2H6, SiH4 and H2 are introduced into the PECVD equipment to deposit the P-Poly layer, the deposition temperature is 350° C., the deposition time is 25 min, the gas flow ratio of SiH4, H2 and B2H6 is 1:11:4, and the gas flow rate of H2 is 5000 sccm;

[0109] Among them, the thickness of the BSG layer is 65nm, N2O, SiH4, B2H6 and H2 are introduced into the PECVD equipment to deposit the BSG layer, the deposition temperature is 325°C, the deposition time is 80min, the gas flow ratio of N2O and SiH4 is 7:1, the gas flow ratio of B2H6 and SiH4 is 7:1, and the gas flow rate of H2 is 5000sccm.

[0110] Step 3: Perform the first laser patterning on the cell processed in step 2 to remove the BSG layer of the preset negative electrode region (N region) on the back of the cell;

[0111] The first laser treatment has a power of 75%, a depth of 55 nm, and a width of 500 nm.

[0112] Step 4: thermally oxidize the back side of the cell after the treatment in step 3, so that the P-poly layer exposed in the back N region is oxidized into a BSG layer;

[0113] The thermal oxidation treatment temperature is 800° C., the oxygen flow rate is 12 slm, the pressure is 500 mbar, and the time is 1.5 h.

[0114] Step 5: Perform a second laser patterning on the cell after the treatment in step 4 to remove the newly formed BSG layer and the remaining tunnel oxide layer in the N region, and obtain a cell with a groove in the preset negative electrode region;

[0115] The second laser treatment has a power of 75%, a depth of 125 nm, and a width of 500 nm.

[0116] Example 4

[0117] This embodiment provides a TBC battery preparation method, comprising the following steps:

[0118] Step 1: using the slotted cell prepared in Example 3, a tunnel oxide layer, an N-Poly layer and a PSG layer are sequentially deposited in the slotted area and the Gap area of ​​the cell by PECVD;

[0119] The thickness of the tunnel oxide layer is 0.8 nm. PH3 gas is introduced during the Poly deposition process to achieve in-situ doping. The thickness of the N-Poly layer is 300 nm.

[0120] Wherein, PH3, SiH4 and H2 are introduced into the PECVD equipment to deposit the P-Poly layer, the deposition temperature is 400° C., the deposition time is 40 min, the gas flow ratio of SiH4, H2 and PH3 is 1:1:0.5, and the gas flow rate of H2 is 3000 sccm;

[0121] Among them, the thickness of the PSG layer is 30nm, SiH4, N2O, H2 and PH3 are introduced into the PECVD equipment to deposit the PSG layer, the deposition temperature is 400°C, the deposition time is 70min, the gas flow ratio of N2O and SiH4 is 4:1, the gas flow ratio of PH3 and SiH4 is 3:1, and the gas flow rate of H2 is 3000sccm.

[0122] Step 2: Annealing crystallization, the annealing temperature is 800°C, and the annealing time is 2h;

[0123] Step 3: Performing a third laser patterning on the cell processed in step 2 to remove the PSG layer in the preset positive electrode area and the PSG layer in the Gap area;

[0124] The third laser treatment has a power of 60% and a depth of 30 nm.

[0125] Step 4: Clean and texturize the cell after the treatment in step 3, remove the N-poly layer, tunnel oxide layer, BSG layer in the preset positive electrode area, remove the PSG layer in the preset negative electrode area, and remove the N-poly layer and tunnel oxide layer in the Gap area;

[0126] The reagent used for cleaning and texturing is NaOH solution with a concentration of 0.4%±0.1%.

[0127] Step 5: Prepare aluminum oxide layers on both sides of the battery cell processed in step 4, coat the front and back sides with SiNx films, and then metallize to form a battery.

[0128] Example 5

[0129] This embodiment provides a TBC battery preparation method, comprising the following steps:

[0130] Step 1: using the slotted cell prepared in Example 3, a tunnel oxide layer, an N-Poly layer and a PSG layer are sequentially deposited in the slotted area and the Gap area of ​​the cell by PECVD;

[0131] The thickness of the tunnel oxide layer is 2.0 nm. PH3 gas is introduced during the Poly deposition process to achieve in-situ doping. The thickness of the N-Poly layer is 100 nm.

[0132] Wherein, PH3, SiH4 and H2 are introduced into the PECVD equipment to deposit the P-Poly layer, the deposition temperature is 500° C., the deposition time is 10 min, the gas flow ratio of SiH4, H2 and PH3 is 1:3:0.2, and the gas flow rate of H2 is 6000 sccm;

[0133] Among them, the thickness of the PSG layer is 100nm, SiH4, N2O, H2 and PH3 are introduced into the PECVD equipment to deposit the PSG layer, the deposition temperature is 500°C, the deposition time is 90min, the gas flow ratio of N2O and SiH4 is 6:1, the gas flow ratio of PH3 and SiH4 is 1:1, and the gas flow rate of H2 is 6000sccm.

[0134] Step 2: annealing crystallization, the annealing temperature is 950 ° C, and the annealing time is 0.5h;

[0135] Step 3: Performing a third laser patterning on the cell processed in step 2 to remove the PSG layer in the preset positive electrode area and the PSG layer in the Gap area;

[0136] The third laser treatment has a power of 90% and a depth of 80 nm.

[0137] Step 4: Clean and texturize the cell after the treatment in step 3, remove the N-poly layer, tunnel oxide layer, BSG layer in the preset positive electrode area, remove the PSG layer in the preset negative electrode area, and remove the N-poly layer and tunnel oxide layer in the Gap area;

[0138] The reagent used for cleaning and texturing is NaOH solution with a concentration of 0.4%±0.1%.

[0139] Step 5: Prepare aluminum oxide layers on both sides of the battery cell processed in step 4, coat the front and back sides with SiNx films, and then metallize to form a battery.

[0140] Embodiment 6-8

[0141] This embodiment provides a TBC battery preparation method, comprising the following steps:

[0142] Step 1: using the slotted cells prepared in Examples 1-3 respectively, depositing a tunnel oxide layer, an N-Poly layer and a PSG layer in sequence in the slotted area and the Gap area of ​​the cell by PECVD;

[0143] The thickness of the tunnel oxide layer is 1.4nm. PH3 gas is introduced during the Poly deposition process to achieve in-situ doping. The thickness of the N-Poly layer is 200nm.

[0144] Wherein, PH3, SiH4 and H2 are introduced into the PECVD equipment to deposit the P-Poly layer, the deposition temperature is 450° C., the deposition time is 25 min, the gas flow ratio of SiH4, H2 and PH3 is 1:2:0.3, and the gas flow rate of H2 is 4500 sccm;

[0145] Among them, the thickness of the PSG layer is 65nm, SiH4, N2O, H2 and PH3 are introduced into the PECVD equipment to deposit the PSG layer, the deposition temperature is 450°C, the deposition time is 80min, the gas flow ratio of N2O and SiH4 is 5:1, the gas flow ratio of PH3 and SiH4 is 2:1, and the gas flow rate of H2 is 4500sccm.

[0146] Step 2: Annealing crystallization, the annealing temperature is 900°C, and the annealing time is 1.5h;

[0147] Step 3: Performing a third laser patterning on the cell processed in step 2 to remove the PSG layer in the preset positive electrode area and the PSG layer in the Gap area;

[0148] The third laser treatment has a power of 75% and a depth of 55 nm.

[0149] Step 4: Clean and texturize the cell after the treatment in step 3, remove the N-poly layer, tunnel oxide layer, BSG layer in the preset positive electrode area, remove the PSG layer in the preset negative electrode area, and remove the N-poly layer and tunnel oxide layer in the Gap area;

[0150] The reagent used for cleaning and texturing is NaOH solution with a concentration of 0.4%±0.1%.

[0151] Step 5: Prepare aluminum oxide layers on both sides of the battery cell processed in step 4 and coat SiNx films on the front and back sides, and then metallize to form a battery to obtain the TBC battery of Example 6-8.

[0152] Comparative Example 1

[0153] This comparative example provides a TBC battery slotting method, which is different from Example 3 in that: step 4 uses alkaline solution polishing to remove the P-poly and tunnel oxide layer, wherein the alkaline solution is NaOH.

[0154] Comparative Example 2

[0155] This comparative example provides a TBC battery preparation method, which is different from Example 8 in that:

[0156] In step 1, the slotted battery cell prepared in comparative example 1 is used;

[0157] The rest is consistent with Example 8.

[0158] Test example:

[0159] Test samples: TBC batteries prepared in Examples 4-8 and the TBC batteries in Comparative Example 2.

[0160] Test method: The sample was tested using the Halm system. The test results are shown in Table 1.

[0161] Table 1

[0162] sample Battery conversion efficiency Example 4 26.88% Example 5 26.85% Example 6 26.82% Example 7 26.80% Example 8 26.95% Comparative Example 2 26.75%

[0163] It can be seen from Table 1 that, compared with Comparative Example 2, the conversion efficiency of the TBC battery prepared by the preparation method provided by the embodiment of the present invention is higher.

[0164] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A TBC battery slotting method, characterized in that: The TBC battery slotting method comprises the following steps: A first tunneling oxide layer, a P-Poly layer and a first BSG layer are sequentially prepared on the back side of the battery substrate, and the first BSG layer of the preset negative electrode region is removed by a first laser treatment; The P-Poly layer is then thermally oxidized to oxidize the P-Poly layer in the preset negative electrode region into a second BSG layer, and a second laser treatment is used to remove the second BSG layer and the first tunneling oxide layer in the preset negative electrode region to obtain a battery cell with a groove in the preset negative electrode region.

2. The TBC battery slotting method according to claim 1, characterized in that: Depositing the first tunnel oxide layer, the P-Poly layer and the first BSG layer by using a PECVD process; Preferably, the thickness of the first tunneling oxide layer is 0.8-2.0 nm; Preferably, the thickness of the P-Poly layer is 100-300 nm; Preferably, B2H6, SiH4 and H2 are introduced into a PECVD device to deposit the P-Poly layer, the deposition temperature is 300-400°C, the deposition time is 10-40 min, the gas flow ratio of SiH4, H2 and B2H6 is 1:(9-12):(2-5), and the gas flow rate of H2 is 2000-8000 sccm; Preferably, the thickness of the first BSG layer is 30-100 nm; Preferably, N2O, SiH4, B2H6 and H2 are introduced into the PECVD equipment to deposit the first BSG layer, the deposition temperature is 300-350°C, the deposition time is 70-90min, the gas flow ratio of N2O and SiH4 is (5-9):1, the gas flow ratio of B2H6 and SiH4 is (4-10):1, and the gas flow rate of H2 is 2000-8000sccm.

3. The TBC battery slotting method according to claim 1, characterized in that: The first laser treatment has a power of 60-90%, a depth of 30-80nm, and a width of 400-600nm. The second laser treatment has a power of 60-90%, a depth of 50-200nm, and a width of 400-600nm.

4. The TBC battery slotting method according to claim 1, characterized in that: The thermal oxidation treatment temperature is 700-900° C., the oxygen flow rate is 8-15 slm, the pressure is 300-700 mbar, and the time is 1-2 hours.

5. Application of the TBC battery slotting method according to any one of claims 1 to 4 in the preparation of TBC batteries.

6. A method for preparing a TBC battery, characterized in that: The TBC battery preparation method comprises the following steps: A second tunneling oxide layer, an N-Poly layer and a PSG layer are sequentially prepared in the grooved area and the Gap area of ​​the battery cell obtained by the TBC battery grooved method according to any one of claims 1 to 4, and annealed and crystallized; Removing the PSG layer in the preset positive electrode region and the PSG layer in the Gap region, and then removing the N-poly layer, the second tunnel oxide layer, and the first BSG layer in the preset positive electrode region, and removing the PSG layer in the preset negative electrode region, and removing the N-poly layer and the second tunnel oxide layer in the Gap region; A passivation film is prepared on both sides of the battery cell, and then the battery cell is metallized to prepare a TBC battery.

7. The method for preparing a TBC battery according to claim 6, characterized in that: Depositing the second tunnel oxide layer, the N-Poly layer and the PSG layer by a PECVD process; Preferably, the thickness of the second tunneling oxide layer is 0.8-2.0 nm; Preferably, the thickness of the N-Poly layer is 100-300 nm; Preferably, PH3, SiH4 and H2 are introduced into a PECVD device to deposit the N-Poly layer, the deposition temperature is 400-500° C., the deposition time is 10-40 min, the gas flow ratio of SiH4, H2 and PH3 is 1:(1-3):(0.2-0.5), and the gas flow rate of H2 is 3000-6000 sccm; Preferably, the thickness of the PSG layer is 30-100 nm; Preferably, SiH4, N2O, H2 and PH3 are introduced into the PECVD equipment to deposit the PSG layer, the deposition temperature is 400-500°C, the deposition time is 70-90min, the gas flow ratio of N2O and SiH4 is (4-6):1, the gas flow ratio of PH3 and SiH4 is (1-3):1, and the gas flow rate of H2 is 3000-6000sccm.

8. The method for preparing a TBC battery according to claim 6, characterized in that: The annealing temperature is 800-950° C., and the annealing time is 0.5-2 h.

9. The method for preparing a TBC battery according to claim 6, characterized in that: The PSG layer in the preset positive electrode area and the PSG layer in the Gap area are removed by a third laser treatment; Preferably, the third laser treatment has a power of 60-90% and a depth of 30-80 nm.

10. The method for preparing a TBC battery according to claim 6, characterized in that: A cleaning and texturing process is used to remove the N-poly layer, the second tunneling oxide layer, and the first BSG layer in the preset positive electrode area, the PSG layer in the preset negative electrode area, and the N-poly layer and the second tunneling oxide layer in the Gap area; Preferably, the reagent used for cleaning and texturing is NaOH solution with a concentration of 0.4%±0.1%; Preferably, preparing the passivation film includes preparing an aluminum oxide layer and a silicon nitride layer.

Citation Information

Patent Citations

  • Preparation method of P-type IBC battery

    CN115799391A

  • Silicon-based solar cell and preparation method thereof

    CN116646424A

Cited By

  • Back contact solar cell, preparation method thereof and photovoltaic module

    CN121126950A

  • Integrated back contact solar cell and method for producing an integrated back contact solar cell

    EP4823277A1

  • Interdigitated back contact solar cell and method of producing an interdigitated back contact solar cell

    WO2026215443A1